Spatial Analysis of Soil Salinity in the Indus River Delta, Pakistan - Solangi, G. S.; Siyal, A. A.; Babar, M. M.; Siyal, P. (Engineering, Technology & Applied Science Research, 2019)
Soil salinization is one of the most damaging environmental problems in coastal areas, including Indus River Delta (IRD). Due to the reduction of flow in the Indus basin, saline water from the Arabian Sea is intruding into the IRD and has degraded the agricultural lands drastically. Focusing on the gravity of the problem, the present study was designed to explore the spatial distribution of soil salinity in the IRD. Physicochemical analysis of 375 soil samples randomly collected from 125 different locations within the study area was used. Analysis revealed that for the top 0-20cm of soil, about 66.4% of the samples had electrical conductivity (EC) values, and 72.8% sodium content (ESP) values higher than the FAO guidelines. Similarly, for soil depth of 20-40cm, 60.8% of the EC values, and 72% of ESP exceeded the safe limits. Finally, for 40-60cm of soil depth, 56.8% of the EC values and 79.2% of the ESP values were higher than the safe limits. Spatial analysis revealed that more than 50% of the IRD samples were affected by soil salinity. Reduced freshwater flow and the entry of saline water into the delta may likely be the causes of soil salinity in the IRD.